Penyusunan Laporan Keuangan Berdasarkan SAK EMKM Pada UMKM Rumah Makan Aruza Pontianak - Sabirin, Sabirin; Fitri, Nurul (Faculty Of Islamic Economics and Business, 2023)
This study aims to: 1) implement the preparation of financial statements in accordance with SAK EMKM on MSMEs of Aruza Restaurant. 2) find out what obstacles are faced by MSME actors in implementing SAK EMKM. 3) find out the right solution in overcoming the obstacles faced by MSME actors. The research method used is descriptive method with a qualitative approach. The data used in this study are primary data obtained by direct observation and interviews with MSME actors. Meanwhile, secondary data was obtained from MSME financial reports, research journals, and articles that were used as a guide to understand the research data. From the results of this study, it can be concluded that the Aruza Restaurant MSMEs in preparing their financial statements have not implemented SAK EMKM. The obstacles faced by MSMEs at Aruza Restaurant in preparing financial reports based on SAK EMKM are the lack of knowledge about the preparation of financial statements, the lack of outreach of socialization on how to prepare financial reports in accordance with SAK EMKM. The solution to overcome the obstacles faced by MSMEs at Aruza Restaurant is that MSME actors are expected to collaborate with the MSME community so that they know how to prepare financial reports in accordance with SAK EMKM. Penelitian ini bertujuan untuk : 1) menerapkan penyusunan laporan keuangan yang sesuai dengan SAK EMKM pada UMKM Rumah Makan Aruza. 2) mengetahui kendala apa saja yang dihadapi pelaku UMKM dalam menerapkan SAK EMKM. 3) mengetahui solusi yang tepat dalam mengatasi kendala yang dihadapi pelaku UMKM. Metode penelitian yang digunakan yaitu metode deskriptif dengan pendekatan kualitatif. Data yang digunakan dalam penelitian ini yaitu data primer yang diperoleh dengan cara observasi dan wawancara langsung kepada pelaku UMKM. Sedangkan untuk data sekunder diperoleh dari laporan keuangan UMKM, jurnal penelitian, dan artikel yang digunakan sebagai panduan untuk memahami data penelitian. Dari hasil penelitian ini dapat disimpulkan bahwa UMKM Rumah Makan Aruza dalam penyusunan laporan keuangannya belum menerapkan SAK EMKM. Kendala yang dihadapi UMKM Rumah Makan Aruza dalam penyusunan laporan keuangan berdasarkan SAK EMKM ialah kurangnya pengetahuan mengenai penyusunan laporan keuangan, kurangnya jangkauan sosialisasi mengenai bagaimana penyusunan laporan keuangan yang sesuai dengan SAK EMKM. Solusi untuk mengatasi kendala yang dihadapi UMKM Rumah Makan Aruza diantaranya diharapkan pelaku UMKM dapat berkolaborasi dengan komunitas UMKM supaya mengetahui bagaimana penyusunan laporan keuangan yang sesuai dengan SAK EMKM.